Body composition is prognostic and predictive of ipilimumab activity in metastatic melanoma. Issue 3 (13th February 2020) - Chu, Michael P.; Li, Yuetong; Ghosh, Sunita; Sass, Shelley; Smylie, Michael; Walker, John; Sawyer, Michael B.
Abstract: Background: Body composition is minimally investigated in an immunotherapy era. Specific body composition signals such as myosteatosis may reflect aspects of patients' immunology and thereby their ability to respond to immunotherapies. Ipilimumab is a key checkpoint inhibitor in metastatic melanoma. As an antibody, it may also be more accurately dosed using body composition parameters rather than weight alone. This retrospective study aimed to investigate body composition‐based dosing and outcomes. Methods: Pretreatment computed tomography images from metastatic melanoma, ipilimumab‐treated patients from 2009 to 2014 were used to measure myosteatosis [skeletal muscle radiographic density or SMD, in Hounsfield units (HU)] and surface area (cm 2 ) as previously described. Cut point analysis determined whether a level of ipilimumab dose and myosteatosis demonstrated differences in progression‐free (PFS) and overall survival (OS). Secondary endpoints included objective response rates and toxicities. Results: Of 121 identified, 97 patients were evaluable. Baseline demographics included 56 years median age, 60% male participants, and 23.7% with BRAF mutations. SMD analysis identified cut‐offs of SMD < 42 in those with BMI < 25 kg/m 2 and <20 HU in those with BMI ≥ 25 kg/m 2, respectively. Low SMD patients had poorer median PFS [2.4 vs. 2.7 months, hazard ratio (HR) 1.76, P = 0.008] and OS (5.4 vs. 17.5 months, HR 2.47, P = 0.001), which remained significant in multivariate modelling. High SMD patients had more immune‐related adverse events, better objective response rates (17.9 vs. 3.3%, P = 0.051), and lower baseline neutrophil‐to‐lymphocyte ratio (21 vs. 39%, P = 0.049). Separately, patients receiving <2.03 mg/cm 2 had improved median PFS (3.0 vs. 2.6 months, HR 1.88, P = 0.02) and OS (14.9 vs. 5.7 months, HR 1.98, P = 0.01). Conclusions: Low SMD and receiving >2.03 mg/cm 2 are prognostic of poorer melanoma outcomes post ipilimumab. SMD may identify patients with flawed immunology and predict who may better respond to such therapy. Ipilimumab dosing by skeletal muscle index stands in contrast to weight‐based dosing and may demonstrate a more accurate method of antibody dosing.